PENGARUH LATIHAN TARGET GAMES TERHADAP AKURASI SERVIS PENDEK BACKHAND BULU TANGKIS - Chandra Rizky Ramadhan; Mimi Haetami; Fitriana Puspa Hidasari (Universitas Tanjungpura, 2019)
AbstractThis research is motivated by the accuracy of the short service badminton backhand which is relatively inaccurate due to the lack of variation in training and the lack of specific training to improve the accuracy of short backhand service. The purpose of this study is: to determine the effect of target games training on improving the accuracy of short backhand badminton service. This study uses the form of Pre-Experimental Design, namely one group pretest-posttest design to determine the effect of actions on a group with 12 treatments. This design has a pre-test and posttest to compare the conditions before and after being treated. The subjects in this study were all badminton extracurricular participants in SMP Negeri 7 Sungari Raya with a total of 16 people. The test in this study used the SPSS 25 T-Test. Based on the results of this study can be concluded as follows: There is an effect of Target Games training on the accuracy of short service badminton backhand with a Sig 0,000 <0.05, then the target games training method can be used as an effective training program to improve the accuracy of short backhand service Keywords: Target games exercise, accuracy, backhand short service